2016
DOI: 10.3892/etm.2016.3999
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical features of multiple primary carcinomas of the oral cavity

Abstract: Abstract. The present study aimed to elucidate the clinical characteristics of multiple primary carcinomas of the oral cavity. The clinical records of 1,024 patients who were treated during follow-up for oral cancer at the Department of Stomatology, Henan Provincial People's Hospital, between March 2013 and December 2014 were retrospectively reviewed. The clinical characteristics of 961 patients who developed single primary oral squamous cell carcinoma (SCC) during follow-up and 54 patients who subsequently de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…The risk factors for MPCs in patients with head and neck cancer include an older age, being male, and smoking and alcohol consumption (16). In addition, it has been reported that MPCs most frequently occurred in the keratinized epithelium, such as the gingiva and hard palate (17), which is consistent with the findings in the present case study. However, the patient of the present study had no history of smoking, or alcohol or betel nut use, which suggested that other risk factors may be involved.…”
Section: Discussionsupporting
confidence: 91%
“…The risk factors for MPCs in patients with head and neck cancer include an older age, being male, and smoking and alcohol consumption (16). In addition, it has been reported that MPCs most frequently occurred in the keratinized epithelium, such as the gingiva and hard palate (17), which is consistent with the findings in the present case study. However, the patient of the present study had no history of smoking, or alcohol or betel nut use, which suggested that other risk factors may be involved.…”
Section: Discussionsupporting
confidence: 91%
“…Presence of multiple primary tumours doesn't affect the overall survival as compared to the single primary cancer. In a study conducted by Ya-Dong Li et all it was reported that the disease specific survival rate for multiple primary tumours was reported to be 90.7% and 79.6% at 5 years and 10 years respectively [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the survival was poorer in patients with MPTs that occurred in the esophagus or lung in a nationwide study (24). The incidence of multiple primary tumors varies in every patient with HNC (3,25,26). Although a regular follow-up CT was arranged after treatment of these patients, some patients with hypopharyngeal and esophageal cancers were still diagnosed in a late tumor stage.…”
Section: Discussionmentioning
confidence: 99%